Islamic Homosexualities: Culture, History, and Literature - Murray, Stephen O.; Roscoe, Will (New York University Press, 1997)
Frontmatter -- Contents -- CHAPTER 1. Introduction -- CHAPTER 2. The Will Not to Know -- CHAPTER 3. Precursors of Islamic Male Homosexualities -- CHAPTER 4. Muhammad and Male Homosexuality -- CHAPTER 5. Woman-Woman Love in Islamic Societies -- CHAPTER 6. Vision and Passion -- Chapter 7. Corporealizing Medieval Persian and Turkish Tropes -- Chapter 8. Male Love and Islamic Law in Arab Spain -- Chapter 9. Male Homosexuality, Inheritance Rules, and the Status of Women in Medieval Egypt -- CHAPTER 10. Homosexuality among Slave Elites in Ottoman Turkey -- CHAPTER 11. Male Homosexuality in Ottoman Albania -- CHAPTER 12. The Balkan Sworn Virgin -- CHAPTER 13. Some Nineteenth-Century Reports of Islamic Homosexualities -- CHAPTER 14. Gender-Defined Homosexual Roles in Sub-Saharan African Islamic Cultures -- CHAPTER 15. Institutionalized Gender-Crossing in Southern Iraq -- CHAPTER 16. The Sohari Khanith -- CHAPTER 17. Male Actresses in Islamic Parts of Indonesia and the Southern Philippines -- CHAPTER 18. Two Baluchi Buggas, a Sindhi Zenana, and the Status of Hijras in Contemporary Pakistan -- CHAPTER 19. The Other Side of Midnight -- CHAPTER 20. Not-So-Gay Life in Pakistan in the 1980s and 1990s -- CHAPTER 21. Two Islamic AIDS Education Organizations -- CHAPTER 22. Conclusion -- Appendix -- Authors -- Index